2002
DOI: 10.1073/pnas.102174799
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid receptors and limbic responses to aversive emotional stimuli

Abstract: Functional neuroimaging studies implicate limbic and paralimbic activity in emotional responses, but few studies have sought to understand neurochemical mechanisms which modulate these responses. We have used positron emission tomography to measure -opioid receptor binding, and cerebral blood flow in the same subjects, and demonstrated that the baseline binding potential and the regional cerebral blood flow in the left inferior temporal pole are functionally related. Higher baseline -opioid receptor binding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 43 publications
4
55
0
Order By: Relevance
“…These findings can be seen as in line with neuroimaging studies in depressed patients, which have highlighted low KOR availability in Amy-anterior cingulate cortex-ventral striatal circuitry in the phenotypic expression of dysphoria (Pietrzak et al, 2014) and aberrant MOR signaling in the cortical-amygdalar circuitry in the response to aversive stimuli (Kennedy et al, 2006;Liberzon et al, 2002). They also agree in part with the results of opioid gene expression in post-mortem studies of suicide victims (Hurd et al, 1997).…”
Section: Oprd1supporting
confidence: 80%
“…These findings can be seen as in line with neuroimaging studies in depressed patients, which have highlighted low KOR availability in Amy-anterior cingulate cortex-ventral striatal circuitry in the phenotypic expression of dysphoria (Pietrzak et al, 2014) and aberrant MOR signaling in the cortical-amygdalar circuitry in the response to aversive stimuli (Kennedy et al, 2006;Liberzon et al, 2002). They also agree in part with the results of opioid gene expression in post-mortem studies of suicide victims (Hurd et al, 1997).…”
Section: Oprd1supporting
confidence: 80%
“…The opioid system in the amygdala has been implicated in the modulation of fear (Good and Westbrook, 1995), as well as consolidation of memories and the antinociceptive actions of conditioned stimuli (McGaugh, 1989). In agreement with these modulatory effects, functional imaging studies have shown that activation of receptors is associated with inhibition of amygdala function (Liberzon et al, 2002). However, the mechanisms underlying this inhibition are not understood.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, the physiological actions of upregulation of this current are evident during brief depolarizations, such as during synaptic activation or after somatic puffer application of glutamate. Activation of this current may be the mechanism underlying the reduction in amygdala activity that has been observed during aversive emotional stimuli when receptors in the amygdala are occupied (Liberzon et al, 2002). The amygdala has long been implicated in "emotional" processing and particularly in mediating responses associated with fear and anxiety (LeDoux, 2000;Davis and Whalen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stress-induced opioid release apparently suppressed anxiety both in MDD participants and non-depressed controls. Functional neuroimaging studies suggest that the endogenous opioid system has an anxiolytic role in regions of the temporal lobe that project to the amygdala [35], and suppresses affective states such as sadness [30,51].…”
Section: Effect Of Naltrexone On Moodmentioning
confidence: 99%